2011
DOI: 10.1097/bsd.0b013e3181d47f9f
|View full text |Cite
|
Sign up to set email alerts
|

In-vitro Comparison of the Pullout Strength of 3 Different Thoracic Screw Fixation Techniques

Abstract: In-vitro pullout resistance of thoracic screw fixation does not differ significantly in intrapedicular and extrapedicular insertion techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…Furderer et al . described an alternative insertion method in the thoracic spine, namely the ‘in‐out‐in’ technique, involving a more lateral insertion point with an oblique trajectory, allowing a more lateral insertion because of the sharper angulation, but risking the screw being directed toward the spinal canal . Rosner et al .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Furderer et al . described an alternative insertion method in the thoracic spine, namely the ‘in‐out‐in’ technique, involving a more lateral insertion point with an oblique trajectory, allowing a more lateral insertion because of the sharper angulation, but risking the screw being directed toward the spinal canal . Rosner et al .…”
Section: Discussionmentioning
confidence: 99%
“…Rosner et al . compared this technique with standard insertion techniques and found that there is relatively good fixation strength associated with the pedicle‐rib technique compared with standard thoracic screw fixation . We used the in‐out‐in technique for five screw placements in cases with narrow pedicles.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations